2017
DOI: 10.1088/0256-307x/34/7/070304
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Bound States in a Driven Two-Particle Bose–Hubbard Model with an Impurity

Abstract: We investigate how the driving field affects the bound states in the one-dimensional two-particle Bose–Hubbard model with an impurity. In the high-frequency regime, compared with the static lattice [Phys. Rev. Lett. 109 (2012) 116405], a new type of Floquet bound state can be obtained even for a weak particle–particle interaction by tuning the driving amplitude. Moreover, the localization degree of the Floquet bound molecular state can be adjusted by tuning the driving frequency, and even the Floquet bound mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…When we consider the right boundary of the lattice, we can also obtain the quasienergy of the Floquet-surface state at the right edge, E s 2 = −E s 1 . These quasienergies obtained by asymptotic analysis agree well with those obtained by diagonalizing the Floquet Hamiltonian H f and effective model (15); see Appendix B for more details. Alternately, we can obtain the cutoff value as an approximation of C 1 ,…”
Section: B Asymptotic Phase Boundary and Phase Diagramsupporting
confidence: 78%
See 1 more Smart Citation
“…When we consider the right boundary of the lattice, we can also obtain the quasienergy of the Floquet-surface state at the right edge, E s 2 = −E s 1 . These quasienergies obtained by asymptotic analysis agree well with those obtained by diagonalizing the Floquet Hamiltonian H f and effective model (15); see Appendix B for more details. Alternately, we can obtain the cutoff value as an approximation of C 1 ,…”
Section: B Asymptotic Phase Boundary and Phase Diagramsupporting
confidence: 78%
“…By tailing inhomogeneous hopping rates and applying external sinusoidal driving, Floquet BICs appear as a result of selective destruction of tunneling [13]. As happened in other contexts, moving to the many-particle framework, two-particle Floquet BICs have been predicted to exist in defect-free Hubbard lattices, either in the bulk [15] or at the surface [16]. It has been shown that in the highfrequency limit, the external periodic driving can induce a virtual surface defect in the defect-free semilattice, and thus results in two-particle Floquet-surface BICs [16].…”
Section: Introductionmentioning
confidence: 96%
“…momentum [7,8]. Recently, topological bound states have been found in various systems, such as, Su-Schrieffer-Heeger (SSH) model [9][10][11][12], XXZ chain [13], Haldane model [14], Hofstadter superlattice model [8], Rice-Mele model [7], and Floquet system [15]. Among these models, we note that they may support topological states even in the absence of interaction.…”
Section: Introductionmentioning
confidence: 84%
“…This mechanism is known as Friedrich-Wintgen scenario [14]. There are more specific examples of BIC arising, for example, in anisotropic [28], Floquet [29] or PT-symmetric systems [30,31]. Today the structures with optical BICs are successfully used for filtering, las-ing, sensing and Raman spectroscopy [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%